First record of the stingless bee Tetragonisca buchwaldi (Friese, 1925) (Hymenoptera, Apidae, Meliponini) in Colombia - Jair Alonso-Alarcón; Diego A. Guevara; Catalina Gutiérrez-Chacón (Check List, 2024)
The stingless bee Tetragonisca buchwaldi (Friese, 1925) is documented in Ecuador (1925), Costa Rica (1962), and Panama (1983). This study presents new records for two provinces in Panama and the ﬁrst-ever report of the species in Colombia. This last record was obtained in September 2022 in Chocó Department using pan traps, which were exposed inside the forest. These new records contribute to the general knowledge of Meliponini, mainly in the biogeographic Chocó region where these bees are undersampled.